Galvanic Leaching of Seafloor Massive Sulphides Using MnO2 in H2SO4-NaCl Media - Przemyslaw B. Kowalczuk; Dan Oliric Manaig; Kristian Drivenes; Ben Snook; Kurt Aasly; Rolf Arne Kleiv (Minerals, 2018)
This paper reports the leaching of seafloor massive sulphides (SMS) from the Loki’s Castle area at the Arctic Mid-Ocean Ridge in sulphuric acid with manganese dioxide and sodium chloride. The results presented are of various leaching experiments conducted under different conditions in order to optimise the dissolution of copper and silver. It was shown that the main copper bearing minerals in the SMS were chalcopyrite and isocubanite, while silver could occur as an admixture in the crystallographic lattice of sulphides or as disseminated micro inclusions. Based on the results, the leaching mechanism was discussed and elucidated. It was shown that the dissolution of the SMS was mainly due to galvanic interactions between the primary marine minerals of SMS and manganese dioxide. Addition of sodium chloride promoted the extraction mechanism.